Identification of Mutation of Glucose-6-Phosphate Dehy-drogenase (G6PD) in Iran: Meta- analysis Study. - Mahmood Moosazadeh; Mahmood Nekoei-Moghadam; Maryam Aliram-Zany; Mohammadreza Amiresmaili (Tehran University of Medical Sciences, 2013)
Glucose-6-phosphate dehydrogenase is one of the most common genetic deficiencies, which approximately 400 million people in the world suffer from. According to authors' initial search, numerous studies have been carried out in Iran regarding molecular variants of this enzyme. Thus, this meta-analysis presented a reliable estimation about prevalence of different types of molecular mutations of G6PD Enzyme in Iran.Keywords "glucose 6 phosphate dehydrogenase or G6PD, Mediterranean or Chatham or Cosenza and mutation, Iran or Iranian and their Persian equivalents" were searched in different databases. Moreover, reference list of the published studies were examined to increase sensitivity and to select more studies. After studying titles and abstracts of retrieved articles, excluding the repeated and unrelated ones, and evaluating quality of articles, documents were selected. Data was analyzed using STATA.After performing systematic review, 22 papers were entered this meta-analysis and 1698 subjects were examined concerning G6PD molecular mutation. In this meta-analysis, prevalence of Mediterranean mutation, Chatham mutation and Cosenza mutation in Iran was estimated 78.2%, 9.1% and 0.5% respectively.This meta-analysis showed that in spite of prevalence of different types of G6PD molecular mutations in center, north, north-west and west of Iran, the most common molecular mutations in people with G6PD deficiency in Iran, like other Mediterranean countries and countries around Persian Gulf, were Mediterranean mutation, Chatham mutation and Cosenza mutation. It is also recommended that future studies may focus on races and regions which haven't been taken into consideration up to now.